The anti-allergic effect of Lactobacillus plantarum GUANKE on allergic rhinitis induced by either ragweed pollen or house dust mites in mice - Zhao, Pei; Zhang, Bin; Zhao, Lian S.; Yang, Zhongli; Li, Ming D. (Frontiers in Nutrition, 2025)
BackgroundCurrent treatment strategies for Allergic rhinitis (AR) are often limited by adverse effects and less efficacy. This study aims to evaluate the therapeutic effect of Lactobacillus plantarum GUANKE in either ragweed pollen (RAGW)- or house dust mite (HDM)-induced AR models.MethodsMice were sensitized intraperitoneally with RAGW or HDM on days 0, 7, and 14, followed by daily intranasal challenges with the respective allergen from day 21 to day 49. The treatment group mice were orally administered cetirizine (10 mg/kg) as positive control or three different doses of L. plantarum GUANKE (106, 108, or 101⁰ CFU/mouse) after daily intranasal challenges. From day 21 to day 49, nose-wiping and sneezing frequencies in mice were recorded at 4-day intervals (days 21, 25, 29, 33, 37, 41, 45, 49). The area under the curves (AUC) of nose-wiping frequency, sneezing frequency and their combined frequency was calculated across these time points. On day 50, mice were euthanized for sample collection. Serum IgE levels and Th2 cytokines (IL-4, IL-5, and IL-13) levels in both serum and nasal mucosa were measured by ELISA. Nasal mucosa tissues were also collected for histopathological analysis.ResultsIn both RAGW- and HDM-induced AR models, L. plantarum GUANKE significantly reduced the nose-wiping frequency, sneezing frequency, and their combined frequency in AR mice on day 49 and markedly reduced the AUCs of these frequencies from day 21 to day 49. L. plantarum GUANKE also significantly decreased serum IgE levels and Th2 cytokines (IL-4, IL-5, and IL-13) levels in both serum and nasal mucosa. Moreover, histopathological analysis showed that L. plantarum GUANKE significantly reduced nasal mucosal thickness, eosinophil infiltration, and goblet cell proliferation.ConclusionThis study demonstrated the L. plantarum GUANKE can alleviate AR symptoms induced by RAGW or HDM in mice by inhibiting the levels of IgE and Th2 cytokines as well as restoring the histopathological changes of nasal mucosa.